Speech intelligibility evaluation for mosques - Harun, Mokhtar (2000)
Unlike mosques, few of enclosed room functionality concentrates only on speech. Even though large contemporary mosques are built into rooms such as multipurpose ball, lecture hall, dining hall and library, main prayer areas are still the most vital room in mosques. With least tolerance to appreciable level of background noise, with volume easily exceeded 10,000 cubic-meter, bard and sound reflecting surfaces are everywhere, and with the installation of dome or domes, mosques should be critically design to manifest, besides its aestbetics and thermal comfort values, an excellent acoustics. It is intended for the good of concentration and serenity of worshippers who come into mosques to dwell temporarily for any religious activities. Because of its sole functionality for speech, speech intelligibility evaluation in mosques requires a set of selective approaches compared to that in multi functional enclosed rooms. This paper discusses architectural acoustics of mosques and proposes their speech intelligibility evaluation techniques.